Effect of atrial fibrillation on outcomes in patients with anterior circulation occlusion stroke receiving endovascular therapy - Wu, Weijuan; Pitton Rissardo, Jamir; Nguyen, Thanh N.; Mofatteh, Mohammad; Wei, Hongquan; Liebeskind, David S.; Yang, Shuiquan; Li, Wanquan; Pan, Wanling; Zhou, Sijie; Lai, Yuzheng; Gao, Jianfang; et al. (Frontiers in Aging Neuroscience, 2023)
Objective: Atrial fibrillation is one of the major risk factors of ischemic stroke. Endovascular thrombectomy (EVT) has become the standard treatment for acute ischemic stroke with large vessel occlusion. However, data regarding the impact of AF on the outcome of patients with acute ischemic stroke treated with mechanical thrombectomy are controversial. The aim of our study was to determine whether atrial fibrillation modifies the functional outcome of patients with anterior circulation acute ischemic stroke receiving EVT. Methods: We reviewed 273 eligible patients receiving EVT from January 2019 to January 2022 from 3 comprehensive Chinese stroke centers, of whom 221 patients were recruited. Demographics, clinical, radiological and treatment characteristics, safety outcomes, functional outcomes were collected. Modified Rankin scale (mRS) score ≤ 2 at 90 days was defined as a good functional outcome. Results: In our cohort, 79 patients (35.74%) were eventually found to have AF. Patients with AF were elder (70.08 ± 11.72 vs. 61.82 ± 13.48 years, p = 0.000) and less likely to be males (54.43% vs. 73.94%, p = 0.03). The significant reperfusion rate (modified thrombolysis in cerebral infarction 2b-3) was 73.42% and 83.80% in patients with and without AF, respectively (p = 0.064). The good functional outcome (90-day modified Rankin scale: 0 to 2) rate was 39.24% and 44.37% in patients with and without AF, respectively (p = 0.460) after adjusting multiple confounding factors. There was no difference in the presence of symptomatic intracerebral hemorrhage between the two groups (10.13% vs. 12.68%, p = 0.573). Conclusion: Despite their older age, AF patients achieved similar outcomes as non-AF patients with anterior circulation occlusion treated with endovascular therapy.